Eyes-Free Art: Exploring Proxemic Audio Interfaces For Blind and Low Vision Art Engagement - Rector, Kyle; Salmon, Keith; Thornton, Daniel; Joshi, Neel; Morris, Meredith Ringel (Proceedings of the ACM on Interactive, Mobile, Wearable and Ubiquitous Technology (IMWUT 2017), 2017)
Engagement in the arts is an important component of participation in cultural activities, but remains a largely unaddressed challenge for people with sensory disabilities. Visual arts are generally inaccessible to people with visual impairments due to their inherently visual nature. To address this, we present Eyes-Free Art, a design probe to explore the use of proxemic audio for interactive sonic experiences with 2D artwork. The proxemic audio interface allows a user to move closer and further away from a painting to experience background music, a novel sonification, sound effects, and a detailed verbal description. We conducted a lab study by creating interpretations of five paintings with 13 people with visual impairments and found that participants enjoyed interacting with the artwork. We then created a live installation with a visually impaired artist to iterate on this concept to account for multiple users and paintings. We learned that a proxemic audio interface allows people to feel immersed in the artwork. Proxemic audio interfaces are similar to visual because they increase in detail with closer proximity, but are different because they need a descriptive verbal overview to give context. We present future research directions in the space of proxemic audio interactions.